PROGNOSTIC SIGNIFICANCE OF THE TOTALITY OF CLINICAL, LABORATORY, AND BIOCHEMICAL FACTORS AFFECTING THE SURVIVAL OF PATIENTS RECEIVING PROGRAMMED HEMODIALYSIS (Global Conference on Medical and Health Sciences, 2026)
AbstractThe aim of this study was to perform a comprehensive assessment of the prognostic significance of combined clinical, laboratory, and biochemical factors affecting survival in patients undergoing maintenance hemodialysis. Despite advances in renal replacement therapy, mortality among hemodialysis patients remains unacceptably high, largely due to cardiovascular complications and metabolic disturbances [1,2]. To determine the sensitivity, specificity, and diagnostic performance of an integrated prognostic model, a multivariate receiver operating characteristic (ROC) analysis was performed, which is considered a standard approach for evaluating predictive accuracy in nephrology research [3,4].
Keywords: hemodialysis, survival, ROC analysis, sensitivity, specificity, AUC, prognosis, risk factors.